Naquib al-Attas’s Philosophy in Pesantren Learning: Implications for Gen X Motivation to Provide Higher Education for Their Children - Ridwan Ridwan; Nasikhin Nasikhin; Zainudin Hasan (Sekolah Tinggi Agama Islam Sadra, 2026)
This study aims to reconstruct the concept of Islamic educational philosophy from the perspective of Syed Muhammad Naquib al-Attas and to analyze its implications for the motivation of Generation X parents to continue their children’s education through higher education. This study employs a qualitative approach with a phenomenological design, utilizing in-depth interviews and participatory observation within a Muslim community rooted in the pesantren tradition in the mountainous region of Batang Regency, Central Java. Research findings indicate that educational and religious practices in Islamic boarding schools reflect the concept of ta’dīb (religious guidance), the integration of knowledge and faith, and an awareness of the Islamic worldview as developed by Syed Muhammad Naquib al-Attas. Collective traditions such as the study of Iḥyā’ ‘Ulūm al-Dīn (Islamic teachings), bahtsul masail (religious discourses), manaqiban (religious recitation), and khataman (religious recitation) shape the spiritual orientation of underprivileged communities, allowing religion to be understood not merely as a ritual but as a source of serenity, social solidarity, and resilience. The attitude of nrimo (respect for God), accompanied by effort, gratitude, and mutual support, demonstrates the internalization of adab (good manners) in daily life, particularly in respect for knowledge, scholars, and education. This awareness is also evident in the motivation of parents who continue to strive to send their children to Islamic universities despite facing economic constraints. They understand education as a continuous charity, a path of worship, and a means of developing civilized individuals with a future orientation and moral responsibility. The choice of sharia, da‘wah, and Islamic education demonstrates the belief that knowledge must bring blessings and social benefits. This finding challenges the habits of modern society which views happiness through material accumulation, but through inner peace, strengthening of faith, and the pursuit of knowledge as a spiritual path to God’s pleasure.